Correspondence between practitioners’ self-assessment and independent motivational interviewing treatment integrity ratings - Beckman, Maria; Lindqvist, Helena; Öhman, Lina; Forsberg, Lars; Lundgren, Tobias; Ghaderi, Ata (Frontiers in Psychology, 2022)
As evaluation of practitioners’ competence is largely based on self-report, accuracy in practitioners' self-assessment is essential for ensuring high quality treatment-delivery. The aim of this study was to assess the relationship between independent observers’ ratings and practitioners’ self-reported treatment integrity ratings of Motivational interviewing (MI). Practitioners (N = 134) were randomized to two types of supervision (i.e., regular institutional group supervision, or individual telephone supervision based on the MI Treatment Integrity (MITI) code). The mean age was 43.2 years (SD = 10.2), and 62.7 percent were females. All sessions were recorded and evaluated with the MITI, and the MI skills were self-assessed with a questionnaire over a period of twelve months. The associations between self-reported and objectively assessed MI skills were overall weak, but increased slightly from baseline to the 12-months assessment. However, the self-ratings from the group that received monthly objective feedback were not more accurate than those participating in regular group supervision. These results expand findings from previous studies and have important implications for assessment of practitioners' treatment fidelity: Practitioners may learn to improve the accuracy of self-assessment of competence, but to ensure that patients receive intended care, adherence and competence should be assessed objectively.